2019
DOI: 10.1097/mcp.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire smoke exposure under climate change

Abstract: Purpose of review-In this review, we describe the current status of the literature regarding respiratory health related to wildfire smoke exposure, anticipated future impacts under a changing climate, and strategies to reduce respiratory health impacts of wildfire smoke. Recent Findings-Recent findings confirm associations between wildfire smoke exposure and respiratory health outcomes, with the clearest evidence for exacerbations of asthma. Although previous evidence showed a clear association between wildfir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 56 publications
(45 reference statements)
2
65
0
6
Order By: Relevance
“…general ambient particulate matter (PM) and respiratory and cardiovascular disease, scientific evidence is lacking for wildfire smoke associations with outcomes other than asthma and chronic obstructive pulmonary disease [3][4][5]. More specifically, studies of single fires in California have reported limited associations between wildfire PM exposure and cardiovascular hospitalizations [6,7] and reductions in birthweight [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…general ambient particulate matter (PM) and respiratory and cardiovascular disease, scientific evidence is lacking for wildfire smoke associations with outcomes other than asthma and chronic obstructive pulmonary disease [3][4][5]. More specifically, studies of single fires in California have reported limited associations between wildfire PM exposure and cardiovascular hospitalizations [6,7] and reductions in birthweight [8].…”
mentioning
confidence: 99%
“…Accordingly, novel studies examining multi-fire periods with additional wildfire exposure metrics are needed to characterize associations in vulnerable groups and to establish a scientific basis for action to minimize smoke exposure. One reason for the limited number of epidemiologic studies of wildland fire air emissions is related to the need for better exposure assessment techniques, including modeling, stationary monitoring, remote sensing, or low cost sensors [3,13,14]. The purposes of this study are to estimate county level exposures to wildland fire-PM for California and to examine the strengths and limitations of using chemical transport models for health studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…smoke, the larger the exposure (Reid and Maestas 2019). Furthermore, fine PM levels in the areas surrounding wildfires have been observed at approximately 400ug/m 3 for daily concentrations, which is substantially higher than the NAAQS and thus presents a respiratory health risk.…”
Section: Wildfire Wood and Biomass Smokementioning
confidence: 98%
“…Consequently, the impact of wildfire smoke on health will be increased in a near future. ( 1 ) Hence, it is to be expected that, knowing the increasing in frequency and intensity of extreme climate conditions, policies would be designed and implemented to prevent wildfires, along with public health strategies to coping smoke inhalation and to respond efficiently to their ravages.…”
mentioning
confidence: 99%